VD_FINDINFO Jug / 2023 / 419 vom 6. April 2023 - VD Tribunal cantonal (2023)
VIOLATION DU SECRET DE FONCTIONDROIT PÉNAL, ABUS D'AUTORITÉ, ADMISSION DE LA DEMANDE | 312 CP, 320 CP, 46 al. 1 CP, 47 CP, 49 CP